2023
DOI: 10.1002/mp.16536
|View full text |Cite
|
Sign up to set email alerts
|

AAPM Task Group Report 307: Use of EPIDs for Patient‐Specific IMRT and VMAT QA

Abstract: PurposeElectronic portal imaging devices (EPIDs) have been widely utilized for patient‐specific quality assurance (PSQA) and their use for transit dosimetry applications is emerging. Yet there are no specific guidelines on the potential uses, limitations, and correct utilization of EPIDs for these purposes. The American Association of Physicists in Medicine (AAPM) Task Group 307 (TG‐307) provides a comprehensive review of the physics, modeling, algorithms and clinical experience with EPID‐based pre‐treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 152 publications
(312 reference statements)
2
8
0
Order By: Relevance
“…The presence of the offset in our study led to the use of the change in standard deviation in dose instead of a gamma analysis and demonstrates the importance of assessing the metrics and tolerances needed for the specific local context to account for the limitations and performance of the IVD software and equipment in use. This is as recommended in Dogan et al (2023) and our novel tolerance metric is reported here in line with recommendations in the report that the sharing of clinical experience and tolerance levels should be encouraged to help inform others on likely performance ranges. Indeed, where the comparison is a 3D dose distribution based upon the planning CT scan instead of an ontreatment CBCT, gamma may not be an appropriate metric to use in any case because a change in dose measured at the EPID panel does not necessarily relate directly to an equivalent change in dose within the patient (for example in the case of significant shape change).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The presence of the offset in our study led to the use of the change in standard deviation in dose instead of a gamma analysis and demonstrates the importance of assessing the metrics and tolerances needed for the specific local context to account for the limitations and performance of the IVD software and equipment in use. This is as recommended in Dogan et al (2023) and our novel tolerance metric is reported here in line with recommendations in the report that the sharing of clinical experience and tolerance levels should be encouraged to help inform others on likely performance ranges. Indeed, where the comparison is a 3D dose distribution based upon the planning CT scan instead of an ontreatment CBCT, gamma may not be an appropriate metric to use in any case because a change in dose measured at the EPID panel does not necessarily relate directly to an equivalent change in dose within the patient (for example in the case of significant shape change).…”
Section: Discussionsupporting
confidence: 69%
“…This can make it difficult to interpret IVD results in isolation or to set useful tolerances using standard dose comparison metrics such as gamma. This paper demonstrates the importance of using metrics that are appropriate to the particular IVD system in use, a topic which is discussed in AAPM TG307 (Dogan et al 2023), and reports our findings and tolerances in line with recommendations in that document.…”
Section: Introductionsupporting
confidence: 55%
“…We used a 20% threshold to exclude from the analysis the low‐dose region due to uncertainties in the dose conversion from EPID images. 22 No interpolation was applied to the PRIMO‐estimated dose.…”
Section: Methodsmentioning
confidence: 99%
“…They reported different examples of failing fractions related to deviations in treatment delivery. Both approaches are reported in the recently published report of the Task Group 307 22 on the use of EPID for transit dosimetry.…”
Section: Introductionmentioning
confidence: 99%
“…PSQA can be defined as a pre-treatment process involving measurements to confirm the deliverability and quality of the patient's treatment plan. 1 This ensures that the planned radiation dose aligns with the intended treatment and meets the required quality standards before the actual patient treatment begins. Various factors, such as the wrong position of the multi-leaf collimator (MLC), MLC speed and fluctuations in the linear accelerator (LINAC) output, beam stability, and planning grid size, may contribute to errors in treatment delivery.…”
Section: Introductionmentioning
confidence: 99%